1988
DOI: 10.1071/bi9880015
|View full text |Cite
|
Sign up to set email alerts
|

The Ovariectomized Ewe: Its Contribution to Controlled Breeding

Abstract: The ovariectomized ewe has been used to establish principles and procedures which have proved invaluable in controlled breeding in entire animals. Bioassays in the ovariectomized ewe, using the end-point of oestrous behaviour, have been used to identify potent and rapidly metabolized progestagens which were subsequently used to control the time of oestrus and ovulation in cyclic ewes effectively, and to induce oestrus and ovulation in anoestrous ewes. Steroid hormone treatment of the ovariectomized ewe has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Therefore, as puberty is normally preceded by a luteal phase (Ronayne, Fitzsimons, Hanrahan, Quirke and Roche, 1991) a deficiency at this time might account for the infertility observed in group A in experiment I. This cannot explain the subfertility of the animals given a single oestrogen and progestagen therapy prior to mating because this treatment would have simulated endocrine changes similar to those that occur during a normal oestrous cycle (Moore, 1988). Furthermore, the subfertility observed in this group was similar to that recorded for pubertal ewes given progestagen/PMSG treatment (Quirke et ah, 1983).…”
Section: Discussionmentioning
confidence: 69%
“…Therefore, as puberty is normally preceded by a luteal phase (Ronayne, Fitzsimons, Hanrahan, Quirke and Roche, 1991) a deficiency at this time might account for the infertility observed in group A in experiment I. This cannot explain the subfertility of the animals given a single oestrogen and progestagen therapy prior to mating because this treatment would have simulated endocrine changes similar to those that occur during a normal oestrous cycle (Moore, 1988). Furthermore, the subfertility observed in this group was similar to that recorded for pubertal ewes given progestagen/PMSG treatment (Quirke et ah, 1983).…”
Section: Discussionmentioning
confidence: 69%
“…Exogenous MAP (Ricketts and Flint, 1980) and progesterone (Moore, 1988) have been used to maintain pregnancy in ovariectomized or otherwise luteally impaired ewes. Parr et al (1992) showed that post-mating supplementation increased the proportion of pregnant ewes only when the ewes were subjected to a nutritional regime which promoted peripheral plasma progesterone deficit through an increased metabolic clearance rate (Parr et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Given their stimulatory (kisspeptin and NKB) and inhibitory (dynorphin) roles in GnRH/LH secretion, we hypothesized that chronic undernutrition, which we have shown suppresses LH secretion in young, castrated male sheep, 49 would inhibit expression of kisspeptin and NKB at the same time as stimulating dynorphin expression in the ARC and within KNDy neurons of OVX sheep. In the present study, we used OVX sheep, a longstanding animal model in reproduction, 50 to directly examine the nutritional effects on LH secretion apart from changes in sensitivity to gonadal steroids. In addition, in the present study, we used maintenance fed females as controls.…”
Section: Introductionmentioning
confidence: 99%